DAMPAK PEMASARAN MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN : (Survei pada Mahasiswa Universitas Pelita Bangsa Angkatan 2023–2024) - Etty Zuliawati Zeed; Ayu Nur Hikmah; Ciska Silvi Oktavia; Almar’atush Sholihah; Siti khunaefah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the impact of social media marketing on consumer purchase decisions, focusing on students of Universitas Pelita Bangsa from the 2023–2024 cohort. Social media has become a dominant marketing tool in the digital era, influencing various aspects of consumer behavior, including purchase decisions. The study employs a survey method with a quantitative approach, involving 150 randomly selected respondents. Data were collected using structured questionnaires measuring social media marketing dimensions such as content, interaction, user engagement, and brand trust. The results reveal that social media marketing significantly influences consumer purchase decisions, with user engagement and brand trust emerging as the most dominant variables. The study concludes that effective social media marketing strategies can enhance purchase decisions, particularly among students. These findings are expected to provide valuable insights for marketers in optimizing digital marketing strategies for the youth consumer segment.